Determination of aroma compounds in pork broth produced by different processing methods. (22nd March 2016) - Wang, Yao; Song, Huanlu; Zhang, Yu; Tang, Jiani; Yu, Donghai
Abstract: The aroma‐active compounds in pork broth cooked by different processing methods were extracted by solid phase micro extraction (SPME) and solvent‐assisted flavour evaporation (SAFE) and analysed by gas chromatography‐olfactometry‐mass spectrometry (GC‐O‐MS). In total, 78 different aroma‐active compounds were tentatively identified in pork broth. Among them, 12 compounds such as ethyl acetate, 3‐(methylthio) propanal, hexanal, 2‐butanone, dimethyl disulfide and dimethyl trisulfide were tentatively identified as predominant aroma‐active compounds in pork broth, according to their high FD value. According to sensory evaluation, the main characteristic flavour of the four samples was the intensely meaty aroma. By investigating the four kinds of pork broth processed by different methods, the broth cooked at 96 °C with air circulation was found to possess stronger meaty aroma and best overall sensory. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : In this paper, 78 different aroma‐active compounds were tentatively identified in pork broth produced by different processing methods. Among them, 12 compounds such as ethyl acetate, 3‐(methylthio)propanal, hexanal, 2‐butanone, dimethyl disulfide and dimethyl trisulfide were tentatively identified as predominant aroma‐active compounds in pork broth. According to sensory evaluation, the broth cooked at 96°C with air circulation was found to possess more meaty aroma and best overall sensory.